2021
DOI: 10.3389/fnsys.2021.674098
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Unilateral and Bilateral Projections From Layers 5 and 6 of the Auditory Cortex to the Inferior Colliculus in Mouse

Abstract: The auditory cortex sends massive projections to the inferior colliculus, but the organization of this pathway is not yet well understood. Previous work has shown that the corticocollicular projection emanates from both layers 5 and 6 of the auditory cortex and that neurons in these layers have different morphological and physiological properties. It is not yet known in the mouse if both layer 5 and layer 6 project bilaterally, nor is it known if the projection patterns differ based on projection location. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Cell surface density seemed appreciably lower in this layer, as well as in layer VI, which could be due to the ascending myelinated fiber bundles reaching for higher cortical target layers, or alternatively to efferent axons leaving A1. Here we also emphasize the potential role of layers V and VI in the descending projections to the inferior colliculus, a pathway yet to be mapped and clarified in dolphins (Vaithiyalingam Chandra Sekaran et al, 2021). Cells of layer VI were arranged rather sparsely with multiform, middle-sized neurons.…”
Section: The General A1 Cytoarchitecture Is Peculiar In Dolphinsmentioning
confidence: 64%
“…Cell surface density seemed appreciably lower in this layer, as well as in layer VI, which could be due to the ascending myelinated fiber bundles reaching for higher cortical target layers, or alternatively to efferent axons leaving A1. Here we also emphasize the potential role of layers V and VI in the descending projections to the inferior colliculus, a pathway yet to be mapped and clarified in dolphins (Vaithiyalingam Chandra Sekaran et al, 2021). Cells of layer VI were arranged rather sparsely with multiform, middle-sized neurons.…”
Section: The General A1 Cytoarchitecture Is Peculiar In Dolphinsmentioning
confidence: 64%
“…For instance, the presence of tonotopic disruption at the level of the midbrain suggests that disruption in the AC may be inherited from lower centers. Alternatively, given the massive feedback to the DCIC from the AC (Asilador and Llano, 2020;Vaithiyalingam Chandra Sekaran et al, 2021;Yudintsev et al, 2021), the tonotopic disruption observed in the current study could be related to disrupted top-down corticocollicular inputs. Future work will be needed to sort out these possibilities.…”
Section: Pcbs Noise and The Central Auditory Systemmentioning
confidence: 84%
“…Therefore, the IC is a good candidate to examine if developmental exposure to PCBs could exacerbate the long-term negative central effects of noise exposure later in adulthood. The IC comprises a major lemniscal division, the central nucleus (ICC), that receives primarily ascending auditory projections (Willard FH and DK, 1983;JF, 2001;DL, 2005), and two non-lemniscal divisions known as the dorsal (DCIC) and lateral (LCIC) cortices that receive massive descending auditory as well as multisensory inputs (Coleman and Clerici, 1987;Saldaña et al, 1996;Winer et al, 1998;Bajo and Moore, 2005;Schreiner and Winer, 2005;Loftus et al, 2008;Lesicko et al, 2016;Vaithiyalingam Chandra Sekaran et al, 2021). To examine the differential impact of PCBs on excitatory vs. inhibitory neurons in the IC, and because the IC is superficially accessible in mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain was then fixed by a subsequent perfusion of 4% PFA. Selected 40 μm coronal sections at the level of the IC were immunostained for NeuN using (NeuN (D4G40) XP® Rabbit mAB, Cell Signaling, Cat# 62994, 1:100) primary antibody and (goat anti-rabbit IgG conjugated to Alexa 405, 1:200) secondary antibody following the immunostaining procedures that were previously described (Issa, Sekaran, & Llano, 2023; Vaithiyalingam Chandra Sekaran et al, 2021). Confocal images were obtained using a Confocal Zeiss LSM 710 Microscope using 10 and 40x objectives and tile scan functions.…”
Section: Methodsmentioning
confidence: 99%